An inquiry into the Quality of Life of People Living in Industrial Area: A Case Study of Cacher Paper Mill. - Das, Sujoy and Roy, Niranjan (2013)
The impact of an industrial set up on QOL of locality is ambiguous and may vary industry-wise. There also exists a wide range of heterogeneity from the externalities point of view. An industry has both positive and negative impact. The present study seeks to evaluate impact of Cachar Paper Mill on the overall quality of life of people living in its proximity. The study is based on primary data which was collected from both industrial and non-industrial zone. After constructing and computing QOL for both industrial zone and non-industrial region we have resorted to ANOVA to test the hypothesis that there is no relationship between quality of life and an industrial set up. The study finds that the average QOL in industrial region is 0.471571 and in the non-industrial region it is 0.390259. The result of ANOVA is significant implying that there is substantial positive relationship between QOL and an industrial set up. However, both ANOVA and regression analysis established that health index (HI) or health related quality of life in industrial region is worse than non-industrial region.